2011
DOI: 10.1159/000329769
|View full text |Cite
|
Sign up to set email alerts
|

Does Automatic Transmission Improve Driving Behavior in Older Drivers?

Abstract: Background: Most older drivers continue to drive as they age. To maintain safe and independent transport, mobility is important for all individuals, but especially for older drivers. Objective: The objective of this study was to investigate whether automatic transmission, compared with manual transmission, may improve the driving behavior of older drivers. Method: In total, 31 older drivers (mean age 75.2 years) and 32 younger drivers – used as a control group (mean age 39.2 years) – were assessed twice on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…The item 'driving too fast' was the error most regularly reported by the occupational therapist, followed by problems with 'gear changing' and 'attention to signs, road lines and traffic lights'. Previous research has shown that driving with an automatic transmission car improves driving performance for older drivers [34] . The most common road situations where errors were observed included 'straight main roads', specifically when it came to speeding, and 'junction to the right and to the left', when it came to attentional errors.…”
Section: Discussionmentioning
confidence: 97%
“…The item 'driving too fast' was the error most regularly reported by the occupational therapist, followed by problems with 'gear changing' and 'attention to signs, road lines and traffic lights'. Previous research has shown that driving with an automatic transmission car improves driving performance for older drivers [34] . The most common road situations where errors were observed included 'straight main roads', specifically when it came to speeding, and 'junction to the right and to the left', when it came to attentional errors.…”
Section: Discussionmentioning
confidence: 97%
“…And third, street lighting at intersections and in front of traffic signals additionally increases safety (Classen, Lopez, et al, 2007;Classen, Shechtman, et al, 2007;Easa et al, 2010;Shechtman et al, 2006). Also, large ES were found for the studies suggesting that in-car tasks such as phoning, pressing buttons, and using in-vehicle information systems decrease driving safety, especially in older drivers (Selander et al, 2012). Such tasks should be avoided or replaced by adequate techniques to reduce risk (Liu, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The studies, however, do not in particular assess the impact of these devices on traffic safety in older drivers. Two studies (Selander, Bolin, & Torbjörn, 2012;Warshawsky-Livne & Shinar, 2002) investigated whether the transmission type (manual vs. automatic) affects driving safety in older drivers. The results are, to some extent, contradictory.…”
Section: Vehicle Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…While checking performance in on-road test on fixed route with manual and automatic transmission. Older drivers commit more errors than younger ones in both conditions 61) .…”
Section: Findings Notementioning
confidence: 91%